Degenrative Fibroid and Sclerosing Peritonitis - Michael Critchley; John Bagley; Pervis Iqbal (Case Reports in Obstetrics and Gynecology)
Sclerosing peritonitis is a rare condition characterised by ascites, peritoneal and bowel wall thickening. Causes reported in the literature include luteal ovarian the comas, peritoneal dialysis, peritoneal chemotherapy and liver cirrhosis. We report an interesting case of a woman presenting with diarrhoea, abdominal distension, ascites and pleural effusion. She was subsequently diagnosed with Sclerosing Peritonitis caused by a degenerating fibroid which was successfully treated by Total Abdominal Hysterectomy and Bilateral Salpingoophrectomy.